The crystal structre of 3-(1-ethenyl-1H-imidazol-3-ium-3-yl)propane-1-sulfonate, C8H12N2O3S - Zhu Yanfang; Xu Guiyang; Song Wenqi; Miao Zongcheng (Zeitschrift für Kristallographie - New Crystal Structures)
C8H12N2O3S, monolinic, P21/n (no. 14), a = 6.0324(5) Å, b = 7.1692(6) Å, c = 21.6655(17) Å, β = 97.022(3)°, V = 929.95(13) Å3, Z = 4, R gt(F) = 0.0409, wR ref(F 2) = 0.1201, T = 193 K.